Situation Report: Romania, 4 August 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. On Guard from East and West Alike / by Michael Shafir Ceausescu Denounces Reforms as Antisocialist, Calls for Warsaw Pact Joint Steps to Contain Them / by Vladimir Socor Ceausescu and the Communist "Rejectionist" Leaders / by Mihai Sturdza Romania Slows Down Its Economic Growth Rate / by Paul Gafton The New Man, Romanian Style / by Dan Ionescu The Poet Mircea Dinescu Complains about Romania's Cultural Tragedy / by Crisula Stefanescu Augustin Buzura's Novel: An Appalling Picture of Romania Today / by Crisula Stefanescu